Comparison of Serum Procalcitonin Levels in Patients with Gram-Negative and Gram-Positive Sepsis - Bukhari, Basma; Naeem, Uzma; Bibi, Afshan; Usman, Javaid; Mustafa, Dr. Qurat ul ain; Bashir, Saima (Pakistan Armed Forces Medical Journal, 2024)
Objective: To compare rise of serum Procalcitonin levels in patients with culture-proven Gram-negative and Gram-positive sepsis. Study Design: Cross-sectional study Place and Duration of Study: Department of Chemical Pathology in collaboration with the Department of Microbiology, Army Medical College at Pak Emirates Military Hospital, Rawalpindi, Pakistan, from Nov 2022 to Nov 2023. Methodology: Five hundred and twenty-four blood samples were analyzed. Blood culture samples were analyzed on the fully automated Biomerieux Bact /Alert 3D system. Bacterial growth was confirmed after incubation at 35°C±2°C ambient air as per Clinical Laboratory Standards Institute guidelines. All samples which showed no growth were discarded after five days. For Procalcitonin analysis, 3ml of peripheral venous blood was collected in a serum plain tube. The serum was separated within 1 hour after collection by centrifugation at 4000rpm. Procalcitonin levels were then measured by Electro-Chemiluminescence immunoassay on the Roche COBAS 6000 chemistry analyzer as per reagent kit literature. Three hundred and seventy-two samples showed growth on blood culture and were included. Results: Out of 372 blood cultures, 195(52.4%) were positive for Gram-negative and 177(47.6%) for Gram-positive isolates. The median serum Procalcitonin levels in Gram-negative group were significantly higher than Gram-positive group (p-value<0.001). ROC curve analysis revealed PCT has a sensitivity of 65.6% and specificity of 78% at a cut-off of 3ng/mL for distinguishing Gram-negative from Gram-positive sepsis. Conclusion: Serum PCT levels were significantly elevated in Gram-negative compared to Gram-positive septicemia.